Whey Proteins Isolate-Based Biopolymeric Combinations to Microencapsulate Supercritical Fluid Extracted Oleoresins from Sea Buckthorn Pomace - Liliana Mihalcea; Iuliana Aprodu; Loredana Dumitrașcu; Elena Iulia Cucolea; George-Mădălin Dănilă; Elena Enachi; Vasilica Barbu; Oana Emilia Constantin; Leontina Grigore-Gurgu; Nicoleta Stănciuc (MDPI AG, 2021)
In this study, high-value, carotenoid-rich oleoresin obtained by supercritical carbon dioxide (SFE-CO2) extraction was used to develop five variants of microencapsulated delivery system, based on whey proteins isolate (WPI), in combination with inulin (I), pectin (P) or lactose (L). The WPI:I and WPI:L variants were also obtained by conjugation via Maillard reaction. The microencapsulation of the SFE-CO2 sea buckthorn pomace oleoresin was performed by emulsion, complex coacervation and freeze-drying, which allowed for the obtaining of five powders, with different phytochemicals profile. The WPI:I conjugate showed the highest level of total carotenoids, whereas the counterpart WPI:L showed the highest content in linoleic acid (46 ± 1 mg/g) and palmitoleic acid (20.0 ± 0.5 mg/g). The β-tocopherol and β-sitosterol were identified in all variants, with the highest content in the conjugated WPI:L variant. Both WPI:L and WPI:I conjugate samples presented similar IC50 value for inhibitory activity against pancreatic lipase and α-amylase; the highest activity was observed for the conjugated WPI:I. The WPI:P combination allowed the highest release of carotenoids in the gastro-intestinal environment. All the powders exhibited poor flowing properties, whereas water activity (aw) ranged from 0.084 ± 0.03 to 0.241 ± 0.003, suggesting that all variants are stable during storage. In case of solubility, significant differences were noticed between non-heated and glycated samples, with the highest value for the WPI:I and the lowest for glycated WPI:I. The structural analysis revealed the presence of finer spherosomes in WPI:I and WPI:L, with a reduced clustering capacity, whereas the particles in the conjugated samples were more uniform and aggregated into a three-dimensional network.